PENGARUH KUALITAS KEHIDUPAN KERJA, PELATIHAN, DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARO - Apriyanti Br. Barus; Winarto Winarto; Selamat Siregar (Universitas Methodist Indonesia, 2023)
The purpose of this study was to determine and analyze the quality of work life, training, and organizational climate on job satisfaction at the Karo Regency Population and Civil Registration Office. The quality of work life, training, organizational climate simultaneously has a positive and significant effect on job satisfaction of the Karo Regency Population and Civil Registration Service employees. the type of data is quantitative data with a saturated sample of 34 respondents. This study concludes that the quality of work life has a partially significant positive effect on job satisfaction of the Karo Regency Population and Civil Registry employees. Partial training has a positive and significant effect on job satisfaction of the Karo Regency Population and Civil Registry Office employees. Partial training has a positive and significant effect on job satisfaction of the Karo Regency Population and Civil Registry Office employees. Adjusted R Square value of 0.921 means 92.1% job satisfaction of Karo Regency Population and Civil Registry employees can be explained by Quality of Work Life, Training, Organizational Climate. While the remaining 7.9% is explained by other factors not examined in this study.